Fertility and survival of Swedish Red and White × Holstein crossbred cows and purebred Holstein cows - Pipino, D. F. (2023)
Swedish Red and White × Holstein (S×H) cows were compared with pure Holstein (HOL) cows for fertility and survival traits in 2 commercial dairy farms in central-southern Córdoba province, Argentina, over 6 years (2008–2013). The following traits were evaluated: first service conception rate (FSCR), overall conception rate (CR), number of services per conception (SC), days open (DO), mortality rate, culling rate, survival to subsequent calvings, and length of productive life (LPL). The data set consisted of 506 lactations from 240 S×H crossbred cows and 1,331 lactations from 576 HOL cows. The FSCR and CR were analyzed using logistic regression, DO and LPL were analyzed using a Cox's proportional hazards regression model, and differences of proportions were calculated for mortality rate, culling rate, and survival to subsequent calvings. The S×H cows were superior to HOL cows in overall lactations for all the fertility traits (+10.5% FSCR, +7.7% CR, −0.5 SC, and 35 fewer DO). During the first lactation, S×H cows were superior to HOL cows for all fertility traits (+12.8% FSCR, +8.0% CR, −0.4 SC, and 34 fewer DO). In the second lactation, S×H cows exhibited lower SC (−0.5) and 21 fewer DO than HOL cows. In the third or greater lactations, S×H cows showed higher FSCR (+11.0%) and CR (+12.2%), lower SC (−0.8), and 44 fewer DO than pure HOL cows. In addition, S×H cows had a lower mortality rate (−4.7%) and a lower culling rate (−13.7%) than HOL cows. Due to the higher fertility and lower mortality and culling rates, the S×H cows had higher survival to the second (+9.2%), third (+16.9%), and fourth (+18.7%) calvings than HOL cows. Because of these results, S×H cows had longer LPL (+10.3 mo) than HOL cows. These results indicate that S×H cows had higher fertility and survival than HOL cows on commercial dairy farms in Argentina.